Students' Critical Thinking Abilities Assessed From the Implementation of the Problem-Based Learning Model: Systematic Literature Review - Ni Nyoman Serma Adi; I Wayan Lasmawan; Desak Putu Parmiti (Jurnal Ilmiah Global Education, 2026)
In the 21st century, critical thinking is a crucial skill that must be developed through effective learning practices. Because it requires students to analyze, formulate, and solve contextual problems, the problem-based learning (PBL) model is considered to enhance their critical thinking skills. The effect of PBL implementation on students' critical thinking skills was examined in the study discussed in this article. Related keywords were used to conduct a search of indexed journal databases (SINTA 2 and Scopus) for the period from 2018 to 2025. A total of eight relevant primary articles were found and evaluated. The results indicate that the majority of studies indicate that PBL implementation improves critical thinking skills. The quality of the problems, the teacher's role as a facilitator, and the use of authentic assessments are key factors contributing to the success. Recommendations for practice and further research are provided.